2019
DOI: 10.1002/mar.21254
|View full text |Cite
|
Sign up to set email alerts
|

Predicting consumers’ cheating behavior. The role of mental representation of goods and psychological ownership

Abstract: This study examines the likelihood of cheating when consumers are offered with the option of using postponed payment plans after purchasing hedonic goods. It addresses how the nature of the good combined with payment timing affects its perceived psychological ownership, which in turn influences consumers’ cheating behavior. Three experimental studies indicate that when consumers mentally represent a hedonic (vs. utilitarian) good, they are more likely to cheat. This effect is greater with a postponed payment t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 52 publications
(73 reference statements)
1
17
0
Order By: Relevance
“…Many studies have explored hedonic consumption, but only a few studies have considered the role of the payment format. A notable example is Viglia et al's (2019) examination of how product type (hedonic vs. utilitarian) and payment timing (in cash immediately or later in instalments) affects consumer's perceived psychological ownership of the product, which influences cheating behavior. Another example is Hoelzl et al (2011), who investigated how payment mode (down payment vs. instalments) affects postpurchase evaluations of hedonic products over time.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies have explored hedonic consumption, but only a few studies have considered the role of the payment format. A notable example is Viglia et al's (2019) examination of how product type (hedonic vs. utilitarian) and payment timing (in cash immediately or later in instalments) affects consumer's perceived psychological ownership of the product, which influences cheating behavior. Another example is Hoelzl et al (2011), who investigated how payment mode (down payment vs. instalments) affects postpurchase evaluations of hedonic products over time.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, with a few exceptions, such as consumer cheating behavior (Viglia, Tassiello, Gordon‐Wilson, & Grazzini, 2019) and post‐purchase product evaluations (Hoelzl, Pollai, & Kastner, 2011), previous research on payment formats has mainly looked at spending (e.g., Prelec & Simester, 2001; Runnemark, Hedman, & Xiao, 2015; Soman, 2003). For example, Soman (2003) found that compared with those who paid with cash, consumers who paid with a less transparent format (e.g., credit card) spend more.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, studies focusing on the object of psychological ownership have gradually emerged. For example, the study by Viglia et al [29] shows that psychological ownership mediates the effects of product attributes (hedonic vs. utilitarian) on consumers' cheating behavior. As a result, the study found that the perceived psychological ownership is lower for hedonic goods and increased consumers' cheating behavior through verifying mediation analysis.…”
Section: The Effect Of Others Investment On Psychological Ownership Dmentioning
confidence: 99%
“…These findings increase our understanding of the influence of individuals' prior consumption experiences on their subsequent behavior. Previous research (Viglia et al, 2019) has shown that after individuals were mentally represented hedonic products, they are more likely to engage in unethical behavior. Our research also suggests that the type of consumption in which individuals engage can affect their subsequent goal‐directed behavior.…”
Section: Discussionmentioning
confidence: 99%